A bespoke contact angle measurement software and experimental setup for determination of surface tension - Soon , Chin Fhong (2013)
Contact angle measurement has wide application in studying the wettability of a surface. This paper presents a contact angle measurement system developed using simple apparatus. The system consists of a bespoke measurement software, USB microscope, motorized linear position slider and a sample holder with back lighting system. The advantages of this system include user friendly, compact size, allow manual and automatic measurements and cost effective. This system is established with the contact angle and surface tension measurement experiment which is based on Fox-Zisman theory. Different probe liquids were suggested and the critical surface tension of polydimethylsiloxane (PDMS) and polyimide were determined using both the software and the hardware system developed.